2007
DOI: 10.1073/pnas.0707413104
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide profiling identifies epithelial cell genes associated with asthma and with treatment response to corticosteroids

Abstract: Airway inflammation and epithelial remodeling are two key features of asthma. IL-13 and other cytokines produced during T helper type 2 cell-driven allergic inflammation contribute to airway epithelial goblet cell metaplasia and may alter epithelial-mesenchymal signaling, leading to increased subepithelial fibrosis or hyperplasia of smooth muscle. The beneficial effects of corticosteroids in asthma could relate to their ability to directly or indirectly decrease epithelial cell activation by inflammatory cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
681
6
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 762 publications
(726 citation statements)
references
References 52 publications
35
681
6
4
Order By: Relevance
“…However, we focused on IL‐13 because it has been well described that the gene expression pattern observed in airway epithelial cells from patients with allergic asthma is well reflected by IL‐13 treatment of cultured primary airway epithelial cells (Woodruff et al. 2007, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, we focused on IL‐13 because it has been well described that the gene expression pattern observed in airway epithelial cells from patients with allergic asthma is well reflected by IL‐13 treatment of cultured primary airway epithelial cells (Woodruff et al. 2007, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…A Th2‐high subtype of asthma has been described and is associated with increased bronchial epithelial expression of periostin ( POSTN ), serpin B2 ( SERPINB2 ), and chloride channel regulator 1 ( CLCA1 ), and predicts a beneficial therapeutic response to corticosteroids (Woodruff et al. 2007, 2009). Recently various clinical trials have shown the potential of inhibitors of Th2 inflammation, including monoclonal antibodies against interleukin (IL)‐13, to modulate clinical outcomes in asthma (van Buul and Taube 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports have shown significant correlations between periostin in serum and eosinophils in sputum [42,43]. Woodruff et al were the first to show upregulated periostin gene expression in bronchoalveolar lavage from patients with asthma as compared to normal control subjects, which was associated with increased concentrations of IL-4, IL-5, and IL-13 [44]. These patients also had higher eosinophil counts in lavage fluid, suggesting that increased periostin levels might reflect a Th2-high profile.…”
Section: Periostinmentioning
confidence: 93%